The effect of collateralizable asset, dispersion of ownership, free cash flow and investment opportunity set on cash dividend of manufacturing companies listed in Indonesia stock exchange - Cut Bella Paramitha; Muhammad Arfan (Proceedings of AICS - Social Sciences, 2017)
This study is aimed to examine the influence of collateralizable asset, dispersion of ownership, free cash flow, and investment opportunity set on cash dividend of manufacturing companies listed in Indonesia Stock Exchange period 2011-2015. The research type used is hypothesis testing study. The time horizon is a balanced panel data for five years (2011-2015). The population in this study is manufacturing companies listed on Indonesia Stock Exchange in 2011-2015. The sampling technique used is purposive sampling method, with the following criteria: (1) manufacturing companies listed on Indonesia Stock Exchange and never de-listed during 2011-2015, (2) manufacturing companies paying dividend on a regular basis in the year 2011-2015. Based on the sampling criteria, the number of samples in this study is 19 companies per year, and thus the number of observations of this study is 95 observations. The data used are secondary data collected from annual report and analyzed by applying standardized regression. The results show that: (1) collateralizable asset has no effect on cash dividend, (2) dispersion of ownership has no effect on cash dividend, (3) free cash flow has positive effect on cash dividend, (4) investment opportunity set has no effect on cash dividend.